Voter's choice of a presidential candidate: An empirical study. Issue 3 (10th December 2020) - Arkorful, Vincent Ekow; Lugu, Benjamin Kweku; Basiru, Ibrahim; Hammond, Anastasia; Arkorful, Vincent Emmanuel; Budu, Godfred
Abstract : Since the consolidation of democracy and the inception of reforms thereof in Ghana, one raging subject matter that has over time come under intense scrutiny, and persistently, altogether eminently preoccupied the attention of political scientists, pollsters, marketers and strategists in particular, has been one bordering on voter's behavior. Understanding voter's behavior is crucially indispensable to reshaping the democratic process and devising political strategies. In spite of this, there is however a paucity of research focus targeted at unraveling the distinct behavior patterns and underpinnings relative to voters' choices. Against this backdrop, the main idea of this research is to explore the antecedents of voters' choice. The theory of consumer behavior has been used as the theoretical framework. Using the survey approach, data was elicited from card bearing registered voters and analyzed with the aid of the structural equation modeling technique. Results of data ( n  = 363) analysis revealed a confluence of voters' choice antecedents anchored on; quality, trust, attractiveness, expertise and image. Based on the results, study implications are discussed, and suggestions for future research are subsequently delineated.